Analysis Of The Free Nutritious Meals Program (MBG) From Pierre Bourdieu’s Perspective: Policy Review And Capital Transformation - Komang Ariyanto; Saharuddin Saharuddin (Institute of Advanced Knowledge and Science, 2026)
The Free Nutritious Meals Program (MBG) is a national strategic policy launched during the administration of President Prabowo Subianto, aimed at improving human resource quality and supporting Indonesia’s Golden Vision 2045. This study analyzes the implementation of MBG from the perspective of Pierre Bourdieu, emphasizing the transformation of habitus, the distribution of economic capital, and the formation of power networks among actors. The analysis was conducted using a literature review approach based on Hannah Snyder (2019) and van der Waldt (2021), covering relevant scientific articles. The findings indicate that the MBG not only functions as a health intervention to reduce stunting prevalence but also as an instrument for transforming nutritional habitus. This is achieved through the internalization of healthy eating patterns, strengthening cultural capital, and reducing social stigma within school environments. The program also builds social capital through the Satuan Pelayanan Pemenuhan Gizi (SPPG), which connects government institutions, schools, MSMEs, and local farmers within region-based food-supply chains. In addition, the program generates economic spillover effects, such as increased income for local producers, job creation, and redistribution of economic capital to the agricultural sector. However, MBG implementation faces various structural and political challenges, including cultural resistance to menus, disparities in service quality, marginalization of school canteen vendors, and the risk of political patronage due to the program’s large budget. Furthermore, geographical barriers, limited logistical infrastructure in disadvantaged, frontier, and outermost (3T) regions, and disinformation in digital spaces may reduce policy legitimacy and hinder equitable capital distribution. In conclusion, the success of MBG depends heavily on transparent governance, locally based logistics decentralization, and strengthened quadruple helix collaboration to ensure that habitus transformation, capital distribution, and economic benefits occur inclusively and sustainably.